Examining the effect of training with a teaching for understanding framework on intravenous therapy administration's knowledge, performance, and satisfaction of nursing students: a non-randomized controlled study - Jing Huang; Xiaoyan Liu; Jing Xu; Li Ren; Lihui Liu; Ting Jiang; Menglu Huang; Zhoupeng Wu (BMC, 2024)
Abstract Background Nursing students require improvement in their intravenous infusion therapy management skills, yet traditional training models possess deficiencies. The Teaching for Understanding (TfU) Framework can enhance the teaching-learning process and support quality education. Therefore, utilizing TfU framework for training may promote the performance of nurses. Methods Utilizing a non-synchronized design, 102 nurses were recruited using a convenience sampling method. Fifty-one student nurses from August 2019 to January 2021 were designated as the control group, and 51 student nurses from February 2021 to July 2022 were included as the intervention group. The control group received traditional teaching methods, while the intervention group was trained based on TfU framework. The impact was gauged through medical education environment perception, theory and practice assessments, and learning satisfaction surveys. Results After the training, there was no significant difference between the control group and the intervention group in the theory assessment. However, the practice assessment scores of the intervention group were significantly higher than those of the control group. Compared with the control group, the learning satisfaction scores of the trained nurses in the intervention group were significantly higher, exhibiting significant differences, particularly in communication ability, teamwork cooperation, summing up capability, and interest in learning improvement. Furthermore, the scores of the learning perceptions, atmosphere, social self-perceptions, and total scores of the intervention group were significantly higher. Conclusion Training using TfU framework can heighten students' understanding and command over knowledge and skills, fuel their learning fervor, and enhance their communication and collaboration abilities. TfU framework should be disseminated in medical education to improve the quality of education.